The genus Rhytidhysteron (Dothideomycetes, Ascomycota) in Mexico - Cobos Villagrán, Aurora; Hernández Rodríguez, César Hugo; Valenzuela, Ricardo; Villa-Tanaca, Lourdes; Calvillo-Medina, Rosa Paulina; Mateo-Cid, Luz Elena; Martínez-Pineda, Michelle; Raymundo, Tania (Instituto de Ecología, A.C., 2020)
Background and Aims: Currently, 21 species associated with the genus Rhytidhysteron are recognized. In Mexico, only Rhytidhysteron rufulum has been reported. The genus is characterized by its navicular to apotecial histerothecia, the margin is striate or smooth; the colours of the epithecium vary from orange-reddish, yellow, green to black and its ascospores present three longitudinal septa. The objective of this study is to carry out a taxonomic review of the genus Rhytidhysteron in Mexico, based on macro- and micromorphological characters. Methods: Ten exploration trips were realized between 2017 to 2019 in several regions of Mexico. In addition, the specimens deposited in the fungus collection of the ENCB herbarium were reviewed. The specimens were studied, described and determined according to traditional mycological techniques. Key results: 381 specimens belonging to the genus Rhytidhysteron were reviewed, of which four species were determined: R. neohysterinum, a new species for science, R. neorufulum and R. thailandicum, new records for the country, and the previously cited R. rufulum. Conclusions: The genus Rhytidhysteron has a high diversity of species in Mexico. Most specimens have been found on decomposing branches, mainly of genera of the Fabaceae family in tropical dry forest, which suggest that this group of plants represent the microhabitat to which Rhytidhysteron species have best adapted.